(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2024)
This review was made about a poem written by its author in the framework of the subject Social work with individuals, which ended up in an essay contest for that same subject at the School of Social Work of the University of Alicante in the 2002 academic year. 2003. Before illustrating the writing, the reviewers’ observations are placed according to different factors.